(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
In consideration of the important impact of plankton body size and Lévy noise on plankton system, a stochastic phytoplankton-zooplankton system with Lévy jump is proposed and investigated in this paper. Firstly, we prove that there is a unique global positive solution to the system by using Lyapunov function and Ito formula. Then, some thresholds which depend on plankton body size are given, and they determine the extinction and weak persistence in the mean of plankton populations. In addition, the sufficient conditions for the existence of a stationary distribution of the solution are given. Finally, some numerical simulations are introduced to support the main theoretical results and illustrate the impact of plankton body size and environmental noise on plankton populations.